2007
DOI: 10.1002/bmb.49
|View full text |Cite
|
Sign up to set email alerts
|

Open‐ended assignments and student responsibility

Abstract: An inquiry-based laboratory course was created in an effort to increase student responsibility in learning and to improve teaching in areas related to molecular medicine. Authentic medical cases with both scientific and clinical aspects formed the basis of a project-oriented course that also included student laboratory work focused on the disease-related proteins. Students used basic biochemical techniques to develop and test hypotheses relating their results to the clinical findings. The course also included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This study would suggest that it is already present in the undergraduate years, although when it develops is not yet clear. It was not apparent in an early interprofessional course involving biomedical students and other students from courses other than medicine (Brauner et al, 2007). Stereotyping or a preconceived notion of the place of other professions in the hierarchy has been observed in a number of other studies of undergraduate health professional students and identified as a barrier in IPE (Cooke et al, 2003;Reeves, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…This study would suggest that it is already present in the undergraduate years, although when it develops is not yet clear. It was not apparent in an early interprofessional course involving biomedical students and other students from courses other than medicine (Brauner et al, 2007). Stereotyping or a preconceived notion of the place of other professions in the hierarchy has been observed in a number of other studies of undergraduate health professional students and identified as a barrier in IPE (Cooke et al, 2003;Reeves, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…The use of an authentic medical case as the basis of the laboratory exercise was intended to reinforce the relevance and application of core course material and demonstrate the potential for collaboration between laboratory‐based scientists and more clinically orientated colleagues. This approach has been shown previously to increase student confidence in problem‐solving and their ability to formulate and test hypotheses .…”
Section: Introductionmentioning
confidence: 98%
“…A review of literature relating to university laboratory provision also described how using open-ended enquiry-based laboratories improved learning outcomes as well as being more enjoyable [12]. Examples of this can be seen throughout bioscience disciplines such as the RNA interference experiments described by Kudell [13], contextualisation of investigations into disease-causing proteins using authentic medical case files [14] and development of a programme for students to work together in small groups on exercise physiology projects [15].…”
Section: Introduction 1practical Science and Meaningful Learningmentioning
confidence: 99%